(6+u)(3u-5)=0

Simple and best practice solution for (6+u)(3u-5)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6+u)(3u-5)=0 equation:


Simplifying
(6 + u)(3u + -5) = 0

Reorder the terms:
(6 + u)(-5 + 3u) = 0

Multiply (6 + u) * (-5 + 3u)
(6(-5 + 3u) + u(-5 + 3u)) = 0
((-5 * 6 + 3u * 6) + u(-5 + 3u)) = 0
((-30 + 18u) + u(-5 + 3u)) = 0
(-30 + 18u + (-5 * u + 3u * u)) = 0
(-30 + 18u + (-5u + 3u2)) = 0

Combine like terms: 18u + -5u = 13u
(-30 + 13u + 3u2) = 0

Solving
-30 + 13u + 3u2 = 0

Solving for variable 'u'.

Factor a trinomial.
(-6 + -1u)(5 + -3u) = 0

Subproblem 1

Set the factor '(-6 + -1u)' equal to zero and attempt to solve: Simplifying -6 + -1u = 0 Solving -6 + -1u = 0 Move all terms containing u to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -1u = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -1u = 0 + 6 -1u = 0 + 6 Combine like terms: 0 + 6 = 6 -1u = 6 Divide each side by '-1'. u = -6 Simplifying u = -6

Subproblem 2

Set the factor '(5 + -3u)' equal to zero and attempt to solve: Simplifying 5 + -3u = 0 Solving 5 + -3u = 0 Move all terms containing u to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3u = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -3u = 0 + -5 -3u = 0 + -5 Combine like terms: 0 + -5 = -5 -3u = -5 Divide each side by '-3'. u = 1.666666667 Simplifying u = 1.666666667

Solution

u = {-6, 1.666666667}

See similar equations:

| .05x+(0.25)0.2x=6.00 | | (y+6)(y+1)=0 | | -4/3*-6= | | (v-6)(v+5)=0 | | 2x+13x=6y+1+7y-1 | | 2x+Q=Px-31 | | u^2-16u=0 | | x-0.55x=4 | | 4xy=3x | | 6-.6y+y=8 | | 8.125/x=6 | | 13=14+-.5x | | -6y+13+9y=8y-(3) | | 5x^2+7x+66=0 | | (4y+2)(5-y)=0 | | -6(x+7)=-4x-(2) | | 7x-16=-3x | | log(2x)=1 | | -7(x+7)=-6 | | 2(u^-1)^-5/-2u^-9 | | 6=-.5(x)+14 | | 2x+1=11x+46 | | -4x-(7)+10x=-7+6x | | 15x(-23)=-45x(-23) | | 2x^4-4=12 | | 0.5(7d+4)=7-(1.5)d | | ln(x+6)-ln(x-5)=6 | | -5(w-8)+9w+3= | | 0.5n=4.5 | | 9u^2+30=0 | | 2.2+x=6.2 | | (x-9)(x+7)=o |

Equations solver categories